Genome-wide identification of colonisation determinants in rhizobium leguminosarum using BarSeq - Knights, H (2021)
Many plant-beneficial bacteria must persist in the rhizosphere and colonise the roots of their host plant to exert their beneficial effects. Plants primarily influence bacterial colonisation of the rhizosphere and roots through modulation of their root exudate composition, whilst bacteria-bacteria interactions affect bacterial persistence and root colonisation through metabolic exchanges, secretion of antimicrobial compounds and other processes. Rhizobium-legume symbioses are one of the best characterised beneficial interactions, due to their potential to alleviate our reliance on nitrogen fertilisers. Despite this, most studies on Rhizobium have focused on its symbiotic lifestyle as an endosymbiont in root nodules and therefore the initial stages of rhizosphere growth and root colonisation remain relatively under characterised.